The infrared spectra of five Philippine volcanic rocks - Timtiman, Angela V.; Pulido, Agustin A. (Quezon City Department of Chemistry, College of Arts and Sciences, University of the Philippines Diliman, 1962)
It has been possible in several instances to correlate the infrared spectra of a sample with its components due to the characteristic absorption bands in the spectra. An attempt is made to correlate the infrared spectra of five Philippine volcanic rocks with their mineral constituents. Two methods of sample preparation--the KBr disc technique and the powder film technique--were used.
The infrared spectra obtained showed two absorption regions. The strong absorption region from about 8.0 to 11.5 microns is characteristic of silicates and phosphates. The weak absorption region at about 12.5 to 14.0 microns is characteristic of silicates but not of phosphates. Silicate is present as the minerals albite, anorthite, quartz and diopside which are the major constituents of the samples, while phosphate is present in a very small amount as apatite. These minerals, however, cannot yet be identified individually from the infrared spectra obtained due to the overlapping of their absorption bands.
Thesis (Bachelor of Science in Chemistry)--University of the Philippines Diliman, October 1962.
Keywords: Infrared spectra; Volcanic rocks